The Analytical Method to Compute the Strain on the Soft PSD in Double-Pulse SRM - Chunguang Wang; Guiyang Xu (International Journal of Aerospace Engineering)
In order to obtain the analytical method to compute the circumferential strain on a soft pulse separation device (PSD), deformation processes of the middle section of the soft PSD, the medicine propellant grain and the case are simplified into a two-dimensional plane strain state. It is found that the main factors affecting the circumferential strain of the soft PSD are the circumferential strain of the inner surface of the propellant grain and the gap between the soft PSD and the propellant grain. In order to study the failure mechanism of the soft PSD in the double-pulse solid rocket motor (SRM), a two-dimensional axisymmetric finite element method (FEM) model of the stress process of the soft PSD is established. The variation of the strain of the soft PSD with the internal pressure load is obtained. It is found that the excessive circumferential strain is the main reason for the failure of the soft PSD. Comparing the analytical calculations with the FEM results, it can be found that the analytical method value is slightly higher than the FEM value, so the analytical method results can be used to initially estimate the circumferential strain of the soft PSD and then predict the rationality and feasibility of the design scheme. In order to further study the failure mechanism of the soft PSD, a micro-CT test of in situ stretching of the soft PSD material is carried out and the variation of porosity and elongation of the material is studied. The test results showed that when the material elongation is large, the microinterface debonding rapidly expands into a penetrating damage, and the PSD structure fails. The conclusions obtained in this paper can provide a useful reference for the design of double-pulse SRM.